Preparation method of printing prime coat white ink for identification card
By using modified polyurethane adhesive, white color paste and polyvinyl alcohol solution on the color card base material, the problems of clear printing on the color card and smooth surface of the white ink are solved, and efficient printing effect and good water resistance and hot press peel strength are achieved.
Patent Information
- Application Number
- CN202411879527.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
It is difficult for the prior art to realize clear text and bright image printing on color card base materials, and the white ink base must have a smooth and delicate surface for easy printing, and it must not change color and deformation under high temperature and pressure.
By polymerizing using dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol, and adding epoxy resin to the polymer for block modification, a long-chain aqueous polyurethane binder was prepared, combined with a white color paste and a polyvinyl alcohol solution, and after mixing and stirring and filtration, a printing primer white ink suitable for color card printing was prepared.
It realizes clear printing on the color card base material, the white ink surface is smooth and delicate, has good water resistance and hot press peeling strength, and does not change color and deformation under high temperature and pressure.
Smart Images

Figure CN119684841A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a printing primer white ink for ID cards. Background Art
[0002] With the popularity of card payment and the pursuit of personalization, major banks and ID card production companies have launched their own personalized cards in order to cater to the functional needs of different groups of people, embarking on the road of "private customization" of ID cards. The previous single white card base material could not adapt to the development of the ID card market, and colorful card bases came into being.
[0003] Personalized ID cards must also ensure the basic information on the card surface, including the text of the issuing bank, card number, personalized pattern, etc. Many colors are easily the same as the color of the color card base material, resulting in blurry and confusing card surface. In order to ensure that the text on the personalized card surface is clear and the image is bright, it is necessary to apply white ink to various color card materials before printing. Not only to cover the base color, but also to ensure that the surface is smooth and delicate after the white ink is applied, so as to facilitate various printing methods. Printing pigments and white ink should complement each other visually, and should not change color or deform under high temperature and pressure.
[0004] The color card substrate is coated with white ink and then printed with patterns, which are then laminated with the adhesive protective film. This ensures that the white ink is bonded to the color card base and integrated with the protective film coating to achieve appropriate peeling strength to meet the wet and hot aging requirements of the card. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a white ink for printing primer for ID cards, so as to make a color card base material suitable for printing various patterns and meet the customization requirements of personalized color ID cards.
[0006] To achieve the above object, the present invention provides a method for preparing a white ink for printing primer for cards, comprising the following steps:
[0007] Dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol are used for polymerization, and epoxy resin is added to the polymer for block modification, methyl ethyl ketone oxime is used to block the opposite end -NCO, and a modified polyurethane prepolymer is obtained by a hydrophilic chain extender, a neutralizing agent is added for neutralization, water is added for emulsification, and hydrazine hydrate is used for chain extension again to obtain a long-chain waterborne polyurethane adhesive;
[0008] Grinding the universal rutile titanium dioxide, nano calcium carbonate and the stabilizer with a ball mill to obtain a white color paste with a percentage of 70-75%;
[0009] Select polyvinyl alcohol with an alcoholysis degree of 88%, dissolve it in boiling water, and filter it through a 300-mesh filter to obtain a 15% polyvinyl alcohol solution;
[0010] The long-chain waterborne polyurethane adhesive, the white color paste, the polyvinyl alcohol solution and the auxiliary agent are mixed and stirred, filtered through a 300-mesh filter, and allowed to stand to obtain a printing primer white ink.
[0011] The specific method of using dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol for polymerization, adding epoxy resin to the polymer for block modification, using methyl ethyl ketone oxime to block the opposite end -NCO, preparing a modified polyurethane prepolymer through a hydrophilic chain extender, adding triethylamine for neutralization, adding water for emulsification, and using hydrazine hydrate for chain extension again to obtain a long-chain waterborne polyurethane adhesive is as follows:
[0012] The polycarbonate diol is melted, vacuum dried, cooled, and dicyclohexylmethane-4,4-diisocyanate is added to form a polymer;
[0013] Adding an organic bismuth catalyst, a hydrophilic chain extender, a crosslinking agent and an epoxy resin to the polymer, raising the temperature, adding acetone to react, and then adding methyl ethyl ketone oxime to keep the temperature to react, so as to obtain a polyurethane prepolymer with a terminal -NCO;
[0014] The polyurethane prepolymer is cooled, a hydrophilic chain extender is added for modification, a neutralizer is added for neutralization, water is added for emulsification, and hydrazine hydrate is used for chain extension again to obtain a long-chain waterborne polyurethane adhesive.
[0015] Among them, the organic bismuth catalyst is a bismuth zinc composite catalyst, the hydrophilic chain extender is dihydroxymethylbutyric acid, accounting for 8.0-10.0% of the mass of the polymer, the cross-linking agent is 1,4-cyclohexanediol and diethanolamine, accounting for 5.0-8.0% and 3.0-5.0% of the mass of the polymer respectively, the epoxy resin accounts for 3.0%-5.0% of the mass of the polymer, and the methyl ethyl ketone oxime accounts for 6.0%-8.0% of the mass of the polymer.
[0016] Wherein, the neutralizing agent is triethylamine, and the triethylamine and the hydrazine hydrate respectively carry out a neutralization reaction and a chain extension reaction at 20-25°C.
[0017] Among them, the general rutile titanium dioxide brand is R902, the nano calcium carbonate is water-based nano calcium carbonate, the compound stabilizer is Livago DA130, and the polyvinyl alcohol brand is 1788.
[0018] The invention discloses a method for preparing a white ink for printing primer for ID cards, comprising the steps of polymerizing dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol, adding epoxy resin to the polymer for block modification, selecting methyl ethyl ketone oxime to block the opposite end -NCO, preparing a modified polyurethane prepolymer through a hydrophilic chain extender, adding a neutralizing agent for neutralization, adding water for emulsification, and then using hydrazine hydrate for chain extension again to obtain a long-chain waterborne polyurethane adhesive; grinding universal rutile titanium dioxide, nano calcium carbonate and a compounding stabilizer by a ball mill to obtain a polyurethane prepolymer containing 100% polyurethane. The amount of the white color paste is 70-75%; polyvinyl alcohol with an alcoholysis degree of 88% is selected, dissolved in boiling water, filtered through a 300-mesh filter to obtain a 15% polyvinyl alcohol solution; the long-chain water-based polyurethane adhesive, the white color paste, the polyvinyl alcohol solution and the auxiliary agent are mixed and stirred, filtered through a 300-mesh filter, and allowed to stand to obtain a printing primer white ink. The method uses a long-chain polyurethane synthesized from dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol, and epoxy resin is added to enhance the crosslinking degree of the polyurethane and improve the water resistance of the white ink. Since epoxy resin is a polyhydroxy compound, it participates in the polycondensation reaction in the copolymerization modification, so that the polyurethane molecules are cross-linked in a network and block copolymerized, which can further improve the peel strength after hot pressing the card. Methyl ethyl ketone oxime is used as a capping agent for polyurethane synthesis. Since -NCO is stably capped and does not participate in the main reaction, the free NCO, urethane bond and polar groups in the film play a bonding role; during the hot pressing period of card making, the -NCO capped by methyl ethyl ketone oxime is unblocked at 110-125℃, and -NCO begins to participate in the reaction, cooperating with other polar covalent bonds to form a bonding interface. When the highest temperature of card making is reached, the reaction is complete and the bonding force reaches the maximum. The bonding strength of different molecular chains is exerted at different temperatures and different time periods, and the use of methyl ethyl ketone oxime for capping makes the prepared white ink have good storage stability. After the white ink is printed, the printing base coating white ink prepared by this method has bright patterns and strong ink fixing ability because the system contains polyvinyl alcohol and methyl cellulose that swell and absorb ink. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The invention provides a method for preparing a white ink for printing primer on a card.
[0021] Figure 2 The invention provides a method for preparing a white ink for printing primer on a card. DETAILED DESCRIPTION
[0022] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0023] See also Figure 1 to Figure 2 The present invention provides a method for preparing a white ink for printing primer for a card, comprising the following steps:
[0024] S1 uses dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol for polymerization, and adds epoxy resin to the polymer for block modification, selects methyl ethyl ketone oxime to block the opposite end -NCO, and obtains a modified polyurethane prepolymer through a hydrophilic chain extender, adds a neutralizing agent for neutralization, adds water for emulsification, and uses hydrazine hydrate for chain extension again to obtain a long-chain waterborne polyurethane adhesive;
[0025] Specific method:
[0026] S11 melts polycarbonate diol, dries in vacuum, cools, and adds dicyclohexylmethane-4,4-diisocyanate to form a polymer;
[0027] In an embodiment of the present invention, polycarbonate diol is melted at 80-85° C., then vacuum dried for 1-2 hours, cooled to 55-65° C., and dicyclohexylmethane-4,4-diisocyanate is added to form a polymer, wherein the mass ratio of dicyclohexylmethane-4,4-diisocyanate to polycarbonate diol in the mixture is 1:0.3-0.5, and then gradually heated to 85-95° C., reacted for 1-2 hours, and then cooled to 40-50° C.
[0028] S12: adding an organic bismuth catalyst, a hydrophilic chain extender, a crosslinking agent and an epoxy resin to the polymer, raising the temperature, adding acetone to react, and then adding methyl ethyl ketone oxime to keep the temperature to react, to obtain a polyurethane prepolymer with a terminal -NCO;
[0029] In an embodiment of the present invention, an organic bismuth catalyst, a hydrophilic chain extender, a cross-linking agent and an epoxy resin are added, wherein the amount of the organic bismuth catalyst is 0.02-0.03% of the mass of the raw material mixture, the temperature is gradually increased to 65-70° C., and then acetone accounting for 20-30% of the mass of the raw material mixture is added, the reaction is carried out for 4-5 hours, the temperature is reduced to 40-50° C., methyl ethyl ketone oxime is added, the reaction is kept at this temperature for 0.5-1 hour, the temperature is increased to 65-70° C. and the reaction is continued for 1.5-2.5 hours, the viscosity of the system is adjusted by acetone, and a polyurethane prepolymer with a terminal -NCO is obtained.
[0030] Among them, the organic bismuth catalyst is a bismuth zinc composite catalyst, the hydrophilic chain extender is dihydroxymethylbutyric acid, accounting for 8.0-10.0% of the mass of the polymer, the cross-linking agent is 1,4-cyclohexanediol and diethanolamine, accounting for 5.0-8.0% and 3.0-5.0% of the mass of the polymer respectively, the epoxy resin accounts for 3.0%-5.0% of the mass of the polymer, and the methyl ethyl ketone oxime accounts for 6.0%-8.0% of the mass of the polymer.
[0031] S13: cooling the polyurethane prepolymer, adding a hydrophilic chain extender for modification, adding a neutralizer for neutralization, adding water for emulsification, and then using hydrazine hydrate for chain extension again to obtain a long-chain waterborne polyurethane adhesive.
[0032] In an embodiment of the present invention, after the polyurethane prepolymer is cooled to 20-30°C, a neutralizer is added, the mass ratio of the neutralizer to the hydrophilic chain extender added to the polyurethane prepolymer is 1:2.0-3.0, and the reaction is carried out for 20-25 minutes. The neutralized polyurethane prepolymer is transferred into a high-speed disperser, and the shear speed of the disperser is set to 1500-2000r / min, so that it is evenly dispersed in deionized water, and the mass ratio of the raw material mixture to deionized water is 1:1.2-1.5. A dimer compound is added dropwise to the dispersion at a rate of 0.03-0.10g / min for a post-chain extension reaction, the mass ratio of the added dimer compound to the added dicyclohexylmethane-4,4-diisocyanate is 1:40-45, and the reaction time lasts for 15-25 minutes to obtain a long-chain waterborne polyurethane for white ink dispersant, and its solid content is 40-45%. The neutralizing agent is triethylamine, and the triethylamine and the hydrazine hydrate respectively carry out a neutralization reaction and a chain extension reaction at 20-25°C.
[0033] S2 uses a ball mill to grind universal rutile titanium dioxide, nano calcium carbonate and a stabilizer to obtain a white color paste with a percentage of 70-75%;
[0034] In the embodiment of the present invention, a general-purpose rutile titanium dioxide, nano calcium carbonate and a dispersant with a compound stabilizer are selected to be pre-dispersed in deionized water by a high-speed disperser, so that the titanium dioxide and nano calcium carbonate are fully wetted under the action of the dispersant. After the pre-dispersed liquid is cooled to room temperature, it is pumped into the cylinder from the upper feed port of the horizontal sand mill through a metering pump. Under the centripetal force generated by the rotating grinding disc, the titanium dioxide and calcium carbonate are ground evenly to form a white color paste. The mass ratio of rutile titanium dioxide and deionized water, nano calcium carbonate, dispersant, and compound stabilizer is 1:0.3-0.4:0.06-0.1:0.04-0.06:0.01-0.03, and the percentage of solids after the white color paste is stabilized is 70-75%, and the dispersant brand is Livago NAP.
[0035] The general rutile titanium dioxide is of R902 grade, the nano calcium carbonate is water-based nano calcium carbonate, the compound stabilizer is Livaco DA130, and the polyvinyl alcohol is of 1788 grade.
[0036] S3 selects polyvinyl alcohol with an alcoholysis degree of 88%, dissolves it in boiling water, and filters it through a 300-mesh filter to obtain a 15% polyvinyl alcohol solution;
[0037] In the embodiment of the present invention, polyvinyl alcohol with an alcoholysis degree of 88% is selected, dissolved in boiling water, and stirred evenly to form a transparent solution with a polyvinyl alcohol content of 15%. The solution is filtered through a 300-mesh filter and set aside.
[0038] S4: Mix and stir the long-chain waterborne polyurethane adhesive, the white color paste, the polyvinyl alcohol solution and the additive, filter through a 300-mesh filter, and let stand to obtain a printing base coating white ink. The polyvinyl alcohol with an alcoholysis degree of 88% is brand 1788.
[0039] In an embodiment of the present invention, the prepared long-chain waterborne polyurethane is placed in a disc high-speed disperser, and the shear speed of the disperser is set to 2500-3000 r / min, and the white color paste, polyvinyl alcohol solution, wetting agent, defoamer, thickener and antistatic agent prepared above are added in sequence, wherein the mass ratio of white color paste, long-chain waterborne polyurethane, polyvinyl alcohol solution, wetting agent, defoamer, thickener and antistatic agent is 55:9.0-11.0:1.4-1.6:0.08- 0.1:0.06~0.08:0.02~0.04:0.02~0.04, mix and stir evenly, filter through a 300-mesh filter, and stand to obtain the card printing primer white ink. The wetting agent is BYK-300 or BYK-306, the defoaming agent is polyoxyethylene pentaerythritol ether or polyoxypropylene glycerol ether; the thickener is any one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and hydroxyethyl cellulose; the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.
[0040] In order to better understand the present technical solution, the following embodiments are provided for further explanation:
[0041] Example 1
[0042] 15g of polycarbonate diol was added to a 500ml four-necked flask, heated to 80°C, then vacuum dried for 1.0 hour, cooled to 55°C, and then 50g of dicyclohexylmethane-4,4-diisocyanate was added, and then gradually heated to 85°C. After reacting for 1 hour, the temperature was lowered to 40°C, 0.013g of bismuth-zinc composite catalyst, 5.20g of hydrophilic chain extender dimethylolbutyric acid, 2.6g of epoxy resin, 3.25g of cross-linking agent 1,4-cyclohexanediol and 1.95g of diethanolamine were added, and the temperature was gradually raised to 65°C, and then 13.0g of acetone was added, and the reaction was continued for 4 hours. The temperature was lowered to 20°C, 4.0 g of methyl ethyl ketone oxime was added, and the reaction was kept at this temperature for 0.5 hour. The temperature was raised to 65°C and the reaction was continued for 1.5 hours. The temperature was then lowered to 20°C, and 10.40 g of triethylamine was added for neutralization. The reaction was continued for 20 minutes. The neutralized product was transferred to a high-speed disperser, and the shear speed of the disperser was set to 1500 r / min. 78.0 g of deionized water was added to the disperser. After stirring for 15 minutes, 1.625 g of chain extender hydrazine hydrate was added dropwise at a rate of 0.03 g / min for secondary chain extension, and the reaction was continued for 15 minutes to obtain 135.60 g of waterborne polyurethane adhesive for standby use.
[0043] 200g of general-purpose rutile titanium dioxide, 12.0g of nano-calcium carbonate, 2.0g of stabilizer and 8.0g of dispersant are pre-dispersed in 60.0g of deionized water by a high-speed disperser. After cooling to room temperature, they are pumped into the cylinder from the upper feed port of the horizontal sand mill through a metering pump. Under the centripetal force generated by the rotating grinding disc, the titanium dioxide and calcium carbonate are ground evenly to form a white color paste for standby use.
[0044] 18.0 g of the prepared waterborne polyurethane adhesive was put into a disc high-speed disperser, and the shear speed of the disperser was set to 2500 r / min. 110.0 g of the white color paste prepared above, 2.8 g of 15% polyvinyl alcohol solution, 0.16 g of wetting agent, 0.12 g of defoaming agent, 0.04 g of thickener and 0.04 g of antistatic agent were added in sequence. After mixing and stirring evenly, the mixture was filtered through a 300-mesh filter screen. After standing, a whitening agent suitable for color card-based printing materials was obtained.
[0045] Example 1 Identification of products and testing of performance effects (at room temperature)
[0046] Table 1 shows the main indicators of the white ink and color card bottom coating white ink printing effect test prepared in this embodiment
[0047]
[0048] Example 1
[0049] The prepared color cards were laminated with PVC tape film, and the hot pressing time was 20 minutes. The humidity of the aging box was 95%, the temperature was 75°C, and the time was 120 hours. Peel strength (T type) test method: According to GB / T14916-2006, ISO / IEC 7810:2003 was used for determination. The test results are shown in Table 2:
[0050] Table 2: Lamination, peeling and aging test of color cards prepared with white ink for printing on ID cards
[0051] project Lamination temperature Lamination pressure Peel strength before aging Peel strength after aging result 138℃ 5MPa 7.8N / CM 7.5N / CM
[0052] Example 2
[0053] 25g of polycarbonate diol was added to a 500ml four-necked flask, heated to 85°C, then vacuum dried for 2.0 hours, cooled to 65°C, and then 50g of dicyclohexylmethane-4,4-diisocyanate was added, and then gradually heated to 95°C. After reacting for 2 hours, the temperature was lowered to 50°C, 0.0225g of bismuth-zinc composite catalyst, 7.50g of hydrophilic chain extender dimethylolbutyric acid, 3.1g of epoxy resin, 7.5g of crosslinking agent 1,4-cyclohexanediol and 3.75g of diethanolamine were added, and the temperature was gradually raised to 70°C, and then 22.5g of acetone was added, and the reaction was continued for 5 hours. The temperature was lowered to 30°C, 5.6 g of methyl ethyl ketone oxime was added, and the reaction was kept at this temperature for 0.5 hour. The temperature was raised to 65°C and the reaction was continued for 1.5 hours. The temperature was then lowered to 20°C, and 22.5 g of triethylamine was added for neutralization. The reaction was continued for 25 minutes. The neutralized product was transferred to a high-speed disperser, and the shear speed of the disperser was set to 2000 r / min. 112.5 g of deionized water was added to the disperser. After stirring for 15 minutes, 1.875 g of chain extender hydrazine hydrate was added dropwise at a rate of 0.10 g / min for secondary chain extension, and the reaction was continued for 15 minutes to obtain 189.50 g of waterborne polyurethane adhesive for standby use.
[0054] 200g of general-purpose rutile titanium dioxide, 20.0g of nano calcium carbonate, 6.0g of stabilizer and 12.0g of dispersant are pre-dispersed in 80.0g of deionized water by a high-speed disperser. After cooling to room temperature, they are pumped into the cylinder from the upper feed port of the horizontal sand mill through a metering pump. Under the centripetal force generated by the rotating grinding disc, the titanium dioxide and calcium carbonate are ground evenly to form a white color paste for standby use.
[0055] 22.0 g of the prepared waterborne polyurethane adhesive was put into a disc high-speed disperser, and the shear speed of the disperser was set to 3000 r / min. 110.0 g of the white color paste prepared above, 3.2 g of 15% polyvinyl alcohol solution, 0.20 g of wetting agent, 0.16 g of defoaming agent, 0.08 g of thickener and 0.08 g of antistatic agent were added in sequence. After mixing and stirring evenly, the mixture was filtered through a 300-mesh filter screen. After standing, a whitening agent suitable for color card-based printing materials was obtained.
[0056] Example 2 Identification of products and testing of performance effects (at room temperature)
[0057] Table 3 shows the main indicators of the white ink and color card bottom-coated white ink printing effect test prepared in this embodiment
[0058]
[0059] The color card prepared in Example 2 was laminated with PVC tape film, and the hot pressing time was 20 minutes. The humidity of the aging box was 95%, the temperature was 75°C, and the time was 120 hours. Peel strength (T type) test method: According to GB / T 14916-2006, ISO / IEC 7810:2003 was used for determination. The test results are shown in Table 4:
[0060] Table 4: Lamination, peeling and aging test of color cards prepared with white ink for printing on ID cards
[0061] project Lamination temperature Lamination pressure Peel strength before aging Peel strength after aging result 138℃ 5MPa 8.3N / CM 7.9N / CM
[0062] Example 3
[0063] 20g of polycarbonate diol was added to a 500ml four-necked flask, heated to 82°C, then vacuum dried for 1.5 hours, cooled to 60°C, and then 50g of dicyclohexylmethane-4,4-diisocyanate was added, and then gradually heated to 90°C. After reacting for 1.5 hours, the temperature was lowered to 45°C, 0.017g of bismuth-zinc composite catalyst, 6.30g of hydrophilic chain extender dimethylolbutyric acid, 3.5g of epoxy resin, 4.30g of cross-linking agent 1,4-cyclohexanediol and 2.19g of diethanolamine were added, and the temperature was gradually raised to 67°C, and then 20.0g of acetone was added, and the reaction was continued for 4.5 hours. The temperature was lowered to 25°C, 6.3 g of methyl ethyl ketone oxime was added, and the reaction was kept at this temperature for 0.5 hour. The temperature was raised to 65°C and the reaction was continued for 1.5 hours. The temperature was then lowered to 20°C, and 16.10 g of triethylamine was added for neutralization. The reaction lasted for 22 minutes. The neutralized product was transferred to a high-speed disperser, and the shear speed of the disperser was set to 1600 r / min. 85.0 g of deionized water was added to the disperser. After stirring for 15 minutes, 1.66 g of chain extender hydrazine hydrate was added dropwise at a rate of 0.05 g / min for secondary chain extension, and the reaction was continued for 15 minutes to obtain 147.30 g of waterborne polyurethane adhesive for standby use.
[0064] 200g of general-purpose rutile titanium dioxide, 16.0g of nano-calcium carbonate, 4.0g of stabilizer and 10.0g of dispersant are pre-dispersed in 70.0g of deionized water by a high-speed disperser. After cooling to room temperature, they are pumped into the cylinder from the upper feed port of the horizontal sand mill through a metering pump. Under the centripetal force generated by the rotating grinding disc, the titanium dioxide and calcium carbonate are ground evenly to form a white color paste for standby use.
[0065] 20.0 g of the prepared waterborne polyurethane adhesive was put into a disc high-speed disperser, and the shear speed of the disperser was set to 2800 r / min. 110.0 g of the white color paste prepared above, 3.1 g of 15% polyvinyl alcohol solution, 0.18 g of wetting agent, 0.14 g of defoaming agent, 0.06 g of thickener and 0.07 g of antistatic agent were added in sequence. After mixing and stirring evenly, the mixture was filtered through a 300-mesh filter screen. After standing, a whitening agent suitable for color card-based printing materials was obtained.
[0066] Example 3 Product identification and performance testing (at room temperature)
[0067] Table 5 shows the main indicators of the white ink and color card bottom-coated white ink printing effect test prepared in this embodiment
[0068]
[0069] The color card prepared in Example 3 was laminated with PVC tape film, and the hot pressing time was 20 minutes. The humidity of the aging box was 95%, the temperature was 75°C, and the time was 120 hours. Peel strength (T type) test method: According to GB / T 14916-2006, ISO / IEC 7810:2003 was used for determination. The test results are shown in Table 6:
[0070] Table 6 Lamination peeling and aging test of color cards prepared by printing white ink for ID cards
[0071] project Lamination temperature Lamination pressure Peel strength before aging Peel strength after aging result 138℃ 5MPa 7.6N / CM 7.3N / CM
[0072] Example 4
[0073] 18g of polycarbonate diol was added to a 500ml four-necked flask, heated to 83°C, then vacuum dried for 1.7 hours, cooled to 62°C, and then 50g of dicyclohexylmethane-4,4-diisocyanate was added, and then gradually heated to 93°C. After reacting for 1.3 hours, the temperature was lowered to 47°C, 0.020g of bismuth-zinc composite catalyst, 7.10g of hydrophilic chain extender dimethylolbutyric acid, 3.0g of epoxy resin, 5.68g of crosslinking agent 1,4-cyclohexanediol and 3.05g of diethanolamine were added, and the temperature was gradually raised to 68°C, and then 18.0g of acetone was added, and the reaction was continued for 4.1 hours. The temperature was lowered to 27°C, 7.2 g of methyl ethyl ketone oxime was added, and the reaction was kept at this temperature for 0.5 hour. The temperature was raised to 65°C and the reaction was continued for 1.5 hours. The temperature was then lowered to 20°C, and 20.50 g of triethylamine was added for neutralization. The reaction lasted for 23 minutes. The neutralized product was transferred to a high-speed disperser, and the shear speed of the disperser was set to 1800 r / min. 91.0 g of deionized water was added to the disperser. After stirring for 15 minutes, 1.715 g of chain extender hydrazine hydrate was added dropwise at a rate of 0.08 g / min for secondary chain extension, and the reaction was continued for 15 minutes to obtain 162.80 g of waterborne polyurethane adhesive for standby use.
[0074] 200g of general-purpose rutile titanium dioxide, 18.0g of nano-calcium carbonate, 5.0g of stabilizer and 19.0g of dispersant are pre-dispersed in 75.0g of deionized water by a high-speed disperser. After cooling to room temperature, they are pumped into the cylinder from the upper feed port of the horizontal sand mill through a metering pump. Under the centripetal force generated by the rotating grinding disc, the titanium dioxide and calcium carbonate are ground evenly to form a white color paste for standby use.
[0075] 19.0 g of the prepared waterborne polyurethane adhesive was put into a disc high-speed disperser, and the shear speed of the disperser was set to 2700 r / min. 110.0 g of the white color paste prepared above, 3.0 g of 15% polyvinyl alcohol solution, 0.17 g of wetting agent, 0.15 g of defoaming agent, 0.05 g of thickener and 0.06 g of antistatic agent were added in sequence. After mixing and stirring evenly, the mixture was filtered through a 300-mesh filter screen. After standing, a whitening agent suitable for color card-based printing materials was obtained.
[0076] Example 4 Identification of products and detection of performance effects (at room temperature)
[0077] Table 7 shows the main indicators of the white ink and color card bottom-coated white ink printing effect test prepared in this embodiment
[0078]
[0079] The color card prepared in Example 4 was laminated with PVC tape film, and the hot pressing time was 20 minutes. The humidity of the aging box was 95%, the temperature was 75°C, and the time was 120 hours. Peel strength (T type) test method: According to GB / T 14916-2006, ISO / IEC 7810:2003 was used for determination. The test results are shown in Table 8:
[0080] Table 8 Lamination peeling and aging test of color cards prepared by printing white ink for ID cards
[0081] project Lamination temperature Lamination pressure Peel strength before aging Peel strength after aging result 138℃ 5MPa 8.5N / CM 8.1N / CM
[0082] The above disclosure is only a preferred embodiment of a method for preparing a white ink for printing base coating on a card of the present invention. Of course, it cannot be used to limit the scope of rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing a white ink for printing primer on a card, characterized in that: The following steps are involved: Dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol are used for polymerization, and epoxy resin is added to the polymer for block modification, methyl ethyl ketone oxime is used to block the opposite end -NCO, and a modified polyurethane prepolymer is obtained by a hydrophilic chain extender, a neutralizing agent is added for neutralization, water is added for emulsification, and hydrazine hydrate is used for chain extension again to obtain a long-chain waterborne polyurethane adhesive; Grinding the universal rutile titanium dioxide, nano calcium carbonate and the stabilizer with a ball mill to obtain a white color paste with a percentage of 70-75%; Select polyvinyl alcohol with an alcoholysis degree of 88%, dissolve it in boiling water, and filter it through a 300-mesh filter to obtain a 15% polyvinyl alcohol solution; The long-chain waterborne polyurethane adhesive, the white color paste, the polyvinyl alcohol solution and the auxiliary agent are mixed and stirred, filtered through a 300-mesh filter, and allowed to stand to obtain a printing primer white ink.
2. The method for preparing the white ink for printing base coating for ID cards as claimed in claim 1, It is characterized by: The specific method of using dicyclohexylmethane-4,4-diisocyanate and polycarbonate diol for polymerization, adding epoxy resin to the polymer for block modification, using methyl ethyl ketone oxime to block the opposite end -NCO, preparing a modified polyurethane prepolymer through a hydrophilic chain extender, adding triethylamine for neutralization, adding water for emulsification, and using hydrazine hydrate for chain extension again to obtain a long-chain waterborne polyurethane adhesive is as follows: The polycarbonate diol is melted, vacuum dried, cooled, and dicyclohexylmethane-4,4-diisocyanate is added to form a polymer; Adding an organic bismuth catalyst, a hydrophilic chain extender, a crosslinking agent and an epoxy resin to the polymer, raising the temperature, adding acetone to react, and then adding methyl ethyl ketone oxime to keep the temperature to react, so as to obtain a polyurethane prepolymer with a terminal -NCO; The polyurethane prepolymer is cooled, a hydrophilic chain extender is added for modification, a neutralizer is added for neutralization, water is added for emulsification, and hydrazine hydrate is used for chain extension again to obtain a long-chain waterborne polyurethane adhesive.
3. The method for preparing the white ink for printing base coating for ID cards as claimed in claim 2, It is characterized by: The organic bismuth catalyst is a bismuth-zinc composite catalyst, the hydrophilic chain extender is dihydroxymethylbutyric acid, which accounts for 8.0-10.0% of the mass of the polymer, the cross-linking agent is 1,4-cyclohexanediol and diethanolamine, which account for 5.0-8.0% and 3.0-5.0% of the mass of the polymer respectively, the epoxy resin accounts for 3.0-5.0% of the mass of the polymer, and the methyl ethyl ketone oxime accounts for 6.0-8.0% of the mass of the polymer.
4. The method for preparing the white ink for printing on cards according to claim 2, characterized in that ; The neutralizing agent is triethylamine, and the triethylamine and the hydrazine hydrate respectively carry out a neutralization reaction and a chain extension reaction at 20-25°C.
5. The method for preparing the white ink for printing primer for ID cards according to claim 1, characterized in that; The general rutile titanium dioxide is of R902 grade, the nano calcium carbonate is water-based nano calcium carbonate, the compound stabilizer is Livaco DA130, and the polyvinyl alcohol is of 1788 grade.